A Multidisciplinary Spine Surgical Indications Conference Leads to Alterations in Surgical Plans in a Significant Number of Cases: A Case Series. Issue 1 (1st January 2021) - Benton, Joshua A.; Mowrey, Wenzhu B.; Ramos, Rafael De La Garza; Weiss, Brandon T.; Gelfand, Yaroslav; Castro-Rivas, Erida; Williams, Lavinia; Headlam, Mark; Udemba, Adaobi; Gitkind, Andrew I.; Krystal, Jonathan D.; Cho, Woojin; et al.
Abstract : Study Design: Case series. Objective: To evaluate the impact of a multidisciplinary spine surgery indications conference (MSSIC) on surgical planning for elective spine surgeries. Summary of Background Data: Identifying methods for pairing the proper patient with the optimal intervention is of the utmost importance for improving spine care and patient outcomes. Prior studies have evaluated the utility of multidisciplinary spine conferences for patient management, but none have evaluated the impact of a MSSIC on surgical planning and decision making. Methods: We implemented a mandatory weekly MSSIC with all spine surgeons at our institution. Each elective spine surgery in the upcoming week is presented. Subsequently, a group consensus decision is achieved regarding the best treatment option based on the expertise and opinions of the participating surgeons. We reviewed cases presented at the MSSIC from September 2019 to December 2019. We compared the surgeon's initial proposed surgery for a patient with the conference attendees' consensus decision on the best treatment and measured compliance rates with the group's recommended treatment. Results: The conference reviewed 100 patients scheduled for elective spine surgery at our indications conference during the study period. Surgical plans were recommended for alteration in 19 cases (19%) with the proportion statistically significant from zero indicated by a binomial test ( P < 0.001). The median absolute change in the invasiveness index of the altered procedures was 3 (interquartile range [IQR] 1–4). Participating surgeons complied with the group's recommendation in 96.5% of cases. Conclusion: In conjunction with other multidisciplinary methods, MSSICs can lead to surgical planning alterations in a significant number of cases. This could potentially result in better selection of surgical candidates and procedures for particular patients. Although long-term patient outcomes remain to be evaluated, this care model will likely play an integral role in optimizing the care spine surgeons provide patients. Level of Evidence: 4 Abstract : Our institution implemented a mandatory weekly multidisciplinary spine surgery indications conference to review all scheduled elective spine surgeries in a given week. The conference recommended alterations to proposed surgical plans in a significant number of cases (19%). Compliance rates with the conference's recommendations were high (96.5%).